2021
DOI: 10.3390/jcm10163662
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia after Open Liver Surgery: Systematic Review of Clinical Evidence

Abstract: Background: The existing recommendations for after open liver surgery, published in 2019, contains limited evidence on the use of regional analgesia techniques. The aim of this systematic review is to summarize available clinical evidence, published after September 2013, on systemic or blended postoperative analgesia for the prevention or treatment of postoperative pain after open liver surgery. Methods: The PUBMED and EMBASE registries were used for the literature search to identify suitable studies. Keywords… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Lower opioid use and lower pain scores with TEA may be due to greater potential for the sympathetic blockade, which may reduce visceral pain resulting during hepatectomy. Somatic and visceral pain during hepatic resection is related to a variety of factors including an incision through the skin, soft tissue, and muscle, rib retraction, as well as diaphragmatic and peritoneal irritation [5]. Somatic pain typically constitutes approximately 70-75% of pain and lasts about 72 hours following open surgery, while visceral pain is typically acute and more intense, lasting for 24-36 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower opioid use and lower pain scores with TEA may be due to greater potential for the sympathetic blockade, which may reduce visceral pain resulting during hepatectomy. Somatic and visceral pain during hepatic resection is related to a variety of factors including an incision through the skin, soft tissue, and muscle, rib retraction, as well as diaphragmatic and peritoneal irritation [5]. Somatic pain typically constitutes approximately 70-75% of pain and lasts about 72 hours following open surgery, while visceral pain is typically acute and more intense, lasting for 24-36 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Open liver resection surgery is associated with intraoperative blood loss, hypotension, coagulopathy, pulmonary complications, liver impairment, and renal impairment, making perioperative pain management challenging [4]. Multimodal analgesic strategies employing regional techniques decrease postoperative pain and opioid consumption following liver resections [5]. Thoracic epidural analgesia (TEA) is considered the 'gold standard' for open thoracic and abdominal surgical procedures [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Patient-controlled intravenous analgesia with opioids is a conventional acute pain therapy with established analgesic efficacy after open hepatectomy. 17 , 18 We, therefore, performed a noninferiority trial to explore whether a safe and easily performed regional analgesia method, ie, continuous ESPB, would provide noninferior pain therapy to opioid PCIA after open liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…The somatic pain caused by the subcostal incision is mainly transmitted via the intercostal nerves T6 to T10, while the visceral pain comes from the coeliac plexus. 18 Although the mechanism of ESPB is controversial, anatomical and clinical studies have suggested that local anesthetic injected into the ESP could spread into the thoracic paravertebral space and proximal intercostal spaces where it acts on the ventral rami of the spinal nerves and intercostal nerves to provide both visceral and somatic analgesia. 19 , 20 However, clinical evidence supports that the patterns of cutaneous sensory blockade often underrepresent the analgesia observed with FPB.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of regional anesthesia in perioperative pain control regimens has been shown to be superior to opioid or non-opioid analgesic modalities alone (4)(5)(6). However, some studies have shown ethnic-based disparities in the use of regional anesthesia (1,(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%